Variabilidade interanual e sazonal na comunidade de Copepoda relacionada ao regime de marés em estuário tropical (Rio Mucuri, Brasil) - Magris, Rafael Almeida (2008)
Copepod community variability among years, seasons and tidal fluctuations at the Mucuri River estuary (Bahia, Brasil) were studied. Zooplankton samples were collected in each season for a period of five years (2002-2006) at three sampling stations; with one of the stations sampled at each tidal cycle (two neap and two flood tides). Temperature, salinity, river flow and rainfall data were obtained. Winter and summer represented the dry and wet seasons, respectively. Copepods abundance ranged from 40 to 63% of the total zooplankton community and was composed of 46 taxa, dominated by common estuarine species such as Temora turbinata, Parvocalanus crassirostris, Acartia lilljeborgi, Oithona hebes, among others). Individuals in all of the life stages were found, exemplifying the role of the estuary in the reproduction and growth of several species. For the stenohaline species (e.g. Notodiaptomus sp. and Thermocyclops minutus), interannual and seasonal variations seems to be more important while for the euryhaline species (the majority of the dominant ones) had their densities controlled by tidal variability.